Effects of solution treatment temperature on the mechanical properties of commercial recycled aluminium alloy cylinder head (A319) - Murizam, Darus (Universiti Malaysia Perlis, 2011)
The present work was performed to investigate the effect of different solution treatment temperature on commercial recycled aluminium alloy cylinder head during artificial ageing process. All samples were sectioned from recycled automotive cylinder head and solution heat treated at 495°C, 510°C and 525°C each for a period of 10 hours. All samples were then quenched into ice water at 0°C and followed by artificial ageing at 180°C for a time up to 20 hours. The precipitation behaviours was monitored by Vicker’s microhardness test and electrical resistivity measurement. Precipitation occurrence were characterised by thermal analysis method and SEM/EDX technique on critical sample. The effect of heat treatment processes was observed by metallographic technique. It is seen that the aluminium alloy exhibit age hardening response similar to artificial ageing where as the the peak-age hardening accelerated when higher solution temperature applied. The hardening effect achieved was due to precipitation of metastable phases of θ˝/θ΄, β˝/β΄, and Q˝Q΄ except for 495°C where the coarser silicon particles contributes to the peak-aged hardening. Silicon particle were fragmentised and spherodised during high temperature solution treatment and homogenised into the aluminium matrix. Prolonged artificial ageing resulting the silicon particles to growth and reduces the nucleation site for phases precipitation, thus reduce the aluminium alloy hardening.